Productivity growth effects of structural reforms: Evidence from developing countries - Kwamivi Gomado (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Which structural reforms affect labour productivity growth in developing countries? This paper answers this question by combining the local projections method and the inverse probability weighted regression adjustment (LP-IPWRA) method. We find that financial reforms, trade reforms, and product market reforms boost labour productivity growth. By documenting the main channels, our results reveal that the reforms studied stimulate labour productivity growth by inducing dynamic efficiency, productive efficiency, and allocative efficiency. However, the results do not find statistical evidence of the ability of reforms to induce structural change. Further analysis taking into account the initial conditions reveals that the impact of reforms is not conditioned by the business cycle, the credit cycle, or whether or not a financial crisis occurs.
Keywords: D24; O16; O24; O47; 330; labour productivity; structural reform; local projection method; business cycle